Governorship and Infrastructural Development - Samardžić, Gligor M; Mlađenović, Marijana Ž. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
The paper presents the data on the governorship of Publius Cornelius Dolabella (14 to 20 A. D.) in the province Gornji Ilirik/Dalmatia. The significant number of epigraphic monuments indicates his activity in this area. These testimonies have important historical value, because they explain political and economical aspects of the West Balkans in the period of the early Principate. At the beginning of his governing career he started to alleviate the consequences caused by the conflicts between the Romans and the domestic people. In his actions and projects in the province of Dalmatia he had in mind the Roman strategic interests and the interests of the inhabitants as well. Peace and development of the province were his main aims. His governorship symbolizes the beginning of the new age in the area of Dalmatia. Numerous epigraphic monuments represent show the developed system of administration for the regulation of territorial and land-ownership relations (inscriptions and forma Dolabelliana). The great infrastructure was built during his governorship, and in this manner the behindhand area of Illyria was approachable and urban. This undoubtedly influenced domestic people and their living in comparison to the previous period. It could be said that the Dolabella united Roman and local interests, so the gap between these interests was bridged. The big projects were completed during Dolabella’s governorship, so the domestic people began to adopt values and achievements of the developed civilizations. It is sure that Publius Cornelius Dolabella contributed to the consolidation of the organization and structure of the Roman province Gornji Ilirik/Dalmatia. In historical context this province approved its functionality; it was a long-lasting administrative formation.